Relationship between bone marrow lesions, cartilage loss and pain in knee osteoarthritis: results from a randomised controlled clinical trial using MRI. Issue 12 (7th July 2010) - Wildi, Lukas Martin; Raynauld, Jean-Pierre; Martel-Pelletier, Johanne; Abram, François; Dorais, Marc; Pelletier, Jean-Pierre
Abstract : Objective: To assess in a multicentre randomised double-blind phase III clinical trial evaluating the effect of licofelone in comparison with naproxen on knee osteoarthritis (OA) the presence of, and change in, bone marrow lesions (BML) over time, their relationship to cartilage volume loss, meniscal extrusion and pain. Methods: Patients with knee OA were selected from the dataset of a recently published randomised controlled trial. MRI was performed at baseline, 6, 12 and 24 months to assess BML score (modified Whole-Organ MRI Score) and cartilage volume changes over time. Pain levels were assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Results: One hundred and sixty-one patients completed the study according to protocol. The global knee and all subregions showed increased BML scores over time (p <0.001, 24 months) except for the medial tibial plateau in the licofelone group. In multivariate regression analysis, licofelone treatment predicted reduction in BML score in the medial tibial plateau (β= −0.280, p = 0.026). BML scores at baseline correlated with cartilage volume over time; however, correlation was limited to 12 months. No positive correlation was found between BML and WOMAC scores. Conclusions: BML scores were found to increase over time, probably owing to accumulation of chronic structural changes. Correlation between BML and cartilage volume was strong at baseline but not over time, probably due to the study drug. Licofelone reduced the BML score in the medial tibial plateau. In contrast to previous reports, no positive relationship was found between BML score (baseline or change over time) and pain, probably an effect of the selected population.